The role of the hybrid court in the Gambia in ensuring accountability for human rights violations during Yahya Jammeh's regime - Killander, Magnus (University of Pretoria, 2024)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2024.